2020
DOI: 10.1186/s40814-020-00722-x
|View full text |Cite
|
Sign up to set email alerts
|

The PLANES study: a protocol for a randomised controlled feasibility study of the placental growth factor (PlGF) blood test-informed care versus standard care alone for women with a small for gestational age fetus at or after 32 + 0 weeks’ gestation

Abstract: Background Stillbirth remains a major concern across the globe and in some high-resource countries, such as the UK; efforts to reduce the rate have achieved only modest reductions. One third of stillborn babies are small for gestational age (SGA), and these pregnancies are also at risk of neonatal adverse outcomes and lifelong health problems, especially when delivered preterm. Current UK clinical guidance advocates regular monitoring and early term delivery of the SGA fetus; however, the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Future studies to identify and validate predictive models in early-onset SGA (EFW <10 th centile <32+0 weeks of gestation) would allow application to a wider population. This would complement the work currently being done in the PLANES study, which is investigating the impact of revealed PlGF in SGA from 32+0 weeks (63). Finally, our primary outcome of fetal or neonatal death provides only short-term information, and data collection for 2-year neurodevelopmental outcomes is on-going.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Future studies to identify and validate predictive models in early-onset SGA (EFW <10 th centile <32+0 weeks of gestation) would allow application to a wider population. This would complement the work currently being done in the PLANES study, which is investigating the impact of revealed PlGF in SGA from 32+0 weeks (63). Finally, our primary outcome of fetal or neonatal death provides only short-term information, and data collection for 2-year neurodevelopmental outcomes is on-going.…”
Section: Discussionmentioning
confidence: 81%
“…Future studies to identify and validate predictive models in early-onset SGA (EFW <10 th centile <32+0 weeks of gestation) would allow application to a wider population. This would complement the work currently being done in the PLANES study, which is investigating the impact of revealed PlGF in SGA from 32+0 weeks (63).…”
Section: Future Directionsmentioning
confidence: 80%
“…Future studies to identify and validate predictive models in early-onset SGA (EFW below the tenth centile, before 32+0 weeks of gestation) would allow application to a wider population. This would complement the work currently being done in the PLANES (placental growth factor led management of the small for gestational age fetus) study, which is investigating the effect of revealed PlGF in SGA from 32+0 weeks (60). Finally, our primary outcome of fetal or neonatal death provides only short-term information, and data collection for 2-year neurodevelopmental outcomes is ongoing.…”
Section: Discussionmentioning
confidence: 92%
“…PLGF awareness was associated with lower perinatal mortality and fewer low birth weight neonates at the expense of increasing respiratory neonatal morbidity without additional burden to the maternal outcome. The value of clinical management according to the PLGF result is currently under investigation by a randomized trial and it is likely that its results will have a strong in uence on the antenatal care [17].…”
Section: Discussionmentioning
confidence: 99%